Predictors of recurrent sprains after an index lateral ankle sprain: a longitudinal study. Issue 4 (December 2018) - Pourkazemi, Fereshteh; Hiller, Claire E.; Raymond, Jacqueline; Black, Deborah; Nightingale, Elizabeth J.; Refshauge, Kathryn M.
Abstract: Objective: To explore and identify the predictors of ankle sprain after an index (first) lateral ankle sprain. Design: Prospective cohort study, Level of evidence II. Setting: Musculoskeletal research laboratory at the University of Sydney. Participants: A sample of convenience (70 controls, 30 with an index sprain) was recruited. Methods: Potential predictors of ankle sprain were measured including: demographic measures, perceived ankle instability, ankle joint ligamentous laxity, passive range of ankle motion, balance, proprioception, motor planning and control, and inversion/eversion peak power. Participants were followed up monthly and the number of ankle sprains was recorded over 12 months. Results: Ninety-six participants completed the study; 10 participants sustained an ankle sprain. A combination of 10 predictors including: a recent index sprain, younger age, greater height and weight, perceived instability, increased laxity, impaired balance, and greater inversion/eversion peak power explained 27 to 56% of the variance in occurrence of ankle sprain ( χ 2 11, 95  = 30.67, p = 0.001). The regression model correctly classified 90% of cases. The strongest independent predictors were history of an index sprain (odds ratio (OR) = 8.23, 95% confidence interval (CI) = 1.66 to 40.72) and younger age (OR = 8.41, 95%CI = 1.48 to 47.96). Conclusion: A recent index ankle sprain and younger age were the only independent predictors of ankle sprain. The combination of greater height or weight, feeling of instability, peak power and impaired balance predicted the occurrence of ankle sprain in almost 90% of participants. These findings could form the basis for intervention targeted at reducing recurrence of sprain after an index sprain.